Rekomendasi Kebijakan untuk Meningkatkan Kesejahteraan Fisik dan Psikologis Ibu Hamil melalui Prenatal Yoga - Riska, Herliana (Indonesian Health Issue, 2025)
Background: Prenatal yoga is a non-pharmacological intervention that offers significant benefits for the physical and psychological well-being of pregnant women. This study aims to explore pregnant women's and healthcare providers' experiences regarding the implementation of prenatal yoga and formulate policy recommendations supporting its integration into antenatal care (ANC) services. Method: This study uses a descriptive qualitative approach with an in-depth interview method with pregnant women, health workers, and heads of health centers. Data were analyzed using triangulation of sources, techniques, and contexts to enhance the validity of findings. NVivo software was employed to facilitate coding and thematic analysis. Result: The results show that prenatal yoga positively impacts stress reduction, body awareness, and childbirth preparation. However, its implementation still faces challenges such as the absence of formal programs, limited information, and lack of regulatory support. Conclusion: Therefore, inclusive health policies, structured training for healthcare workers, and cross-sector collaboration through a pentahelix approach are essential to make prenatal yoga a sustainable and accessible part of routine maternal health services.